A hypothyroid mother after subtotal thyroidectomy delivered a newborn with hyperthyroidism from fetal stage: a case report - Cheng Peng; Weijie Sun; Lixin Fan; Li Li; Xiaojiao Zhang; Ying Gao; Xinlin Hou (BMC, 2022)
Abstract Background Neonatal hyperthyroidism is an extension of fetal disease. Most cases of neonatal hyperthyroidism are transient but may excessively harm multiple organ functions through the actions of maternal thyroid-stimulating hormone receptor antibodies on the neonatal thyroid gland. Case presentation The hyperthyroid mother underwent subtotal thyroidectomy before pregnancy and regularly took levothyroxine to avoid hypothyroidism, but still had a high-level thyroid-stimulating hormone receptor antibody (TRAb). The neonate suffered from hyperthyroidism due to the transplacental TRAb. After a regular medication schedule of an antithyroid drug, combined with a β-blocker to control the ventricular rate, the infant gradually recovered, allowing normal motor and intellectual development. Conclusions Maternal subtotal thyroidectomy cannot prevent the secretion of thyroid receptor antibodies, which may cause either hypothyroidism or hyperthyroidism. The balance between antithyroid drugs and levothyroxine is critical in clinical practice.